(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This paper explores the pedagogical conditions necessary for effectively utilizing innovative technologies to enhance education quality in New Uzbekistan. The study highlights key strategies, challenges, and best practices in integrating modern technologies into the educational process. Through a systematic approach, the research identifies the role of digital tools, teacher training, and institutional policies in fostering a high-quality learning environment. The study also provides a comparative analysis of Uzbekistan’s reforms with global best practices, emphasizing the need for a robust digital infrastructure and sustained teacher development. Additionally, this research investigates the socio-cultural impact of digital learning and provides a roadmap for future advancements in educational innovation.